Pengaruh Persepsi Kemudahan dan Online Customer Review Terhadap Minat Beli Pada Online Store Sociolla - Alifia, Firza Tsamara; Wardhani, Nuruni Ika Kusuma; Fitriyah, Zumrotul (Mahesa Research Center, 2022)
This study aims to determine the effect of perceived convenience and online customer reviews on consumer buying interest in the sociolla online store. Primary data obtained from this study were used in data collection techniques. To approach this problem, the theory from Kotler and Keller, 2016 states that the factors that influence buying interest are the perception of convenience. The method of data collection is by using the survey method. The research method used is quantitative methods with data analysis techniques using Structural Equation Modeling (SEM) and partial least squares (PLS) as analytical tools. This study found that perceived convenience had a significant and positive impact on purchase intention, and online customer reviews had a significant and positive impact on purchase intention.